Respostas fisiológicas de erva-mate (Ilex paraguariensis) cultivada em solução nutritiva com diferentes concentrações de alumínio - Birck, Thalía Preussler (2025)
Ilex paraguariensis, popularly known as yerba mate, is a plant native to temperate regions of Brazil, Paraguay and Argentina. Mate, from the infusion of ground yerba mate leaves, is the most widespread form of consumption of this crop and, on average, 30% of the population of South America ingests more than one liter a day of this drink. This species occurs naturally in soils of low fertility, characterized by high levels of aluminum (Al) and low pH, which does not make it usual to correct the soil for its cultivation. Meanwhile, although mate has phytochemical properties, it can become a source of Al absorption by consumers. The aim of this study was to evaluate I. paraguariensis seedlings in a hydroponic system exposed to concentration different of Al, in order to determine which changes, occur in morphological (leaf area, biomass), photosynthetic (photosynthetic rate, stomatal conductance and transpiration rate), biochemical (pigments, H2O2 content, POD and SOD enzymes, lipid peroxidation of membranes) and metabolic (quantification of secondary metabolites and Al in the leaf infusion). Two experiments were carried out, the first to determine the maximum capacity of days of yerba mate in a hydroponic system with the different treatments, and the second experiment to evaluate the objective physiological variables. Both experiments were conducted in a greenhouse with controlled conditions and a completely randomized design. Yerba mate seedlings approximately 25 cm long were exposed for 18 days to Hoagland and Arnon's nutrient solution with concentrations of 0, 25, 50, 75, 100 and 200 mg L-1 of aluminum and pH of 4.8. On the 18th day of exposure to the Al solution, the morphological and photosynthetic variables were evaluated, in the same period materials were collected for biochemical analysis, quantification of Al in the infusion of leaves, and quantification of secondary metabolites. The data obtained were submitted to analysis of variance and for the significant effects, regression models were adjusted between the independent variable (Al concentrations) and the response variables. Linear models of first and second degrees were explored in order to find the best mathematical model to describe these relationships through the R software. The results of this study are presented in article format and demonstrate that aluminum does not affect morphological and photosynthetic variables and pigment concentrations, but is involved in the production of reactive oxygen species and changes in the amount of compounds of secondary metabolism. Therefore, this information can help in the understanding of future research aimed at more efficient and safer cultivation practices.